Antimicrobial and antispasmodic activities and effect on sexual hormones of chemical substances of Tagetes pusilla ("anisilo") on female rats - Bonilla R., Pablo (2007)
There was studied the specie Tagetes pusilla "anisillo" " saw anise's ", which is a medicine original Asteraceae of use medical of our country, whichgrows abundant in Ayacucho's department, Tambillo's locality, between 2800 to 3000 msnm and which according to the information provided by the etnobotanic, popular medicine, anthropologic information, they indicate its uses as infusions of the air part and its essential oil, for to relieve affections of the digestive tract and for the lactic secretion, besides diuretic. In the present investigation the types detected and identified of secondary metabolits predominant in the extract etanólico of leaves of anisillo, that were fenolics compounds, flavonoids and alkaloids. The antibacterial comparatíve activity decided between the essential oil and the etanólico extract of anisillo, thinking that both showed an antibacterial significant activity. Being verified the activity of the metabolits secondary present in the etanólico extraet of Tagetes's pusilla lea ves on the smooth gastrointestinal muscle, by means of Chidume's et al. methods 2002 with modifications; and that of Akah et al. 1998; as well as the determination of the level of prolactine in rates according to Di Carlo et al. 2005 with modifications, being that the etanólico extract of Tagetes pusilla in the experimental conditions increased the levels of prolactine, estrogens, progesterone, LH, FSH in normal rates; having been demonstrated easing of the duodenum isolated of rat, and was observed an increase of the activity of the ileon of rat, which probably should to the presence of alkaloids.